Efficacy of genetically modified Bt toxins alone and in combinations against pink bollworm resistant to Cry1Ac and Cry2Ab. - Bruce E Tabashnik (Public Library of Science (PLoS), 2013)
Evolution of resistance in pests threatens the long-term efficacy of insecticidal proteins from Bacillus thuringiensis (Bt) used in sprays and transgenic crops. Previous work showed that genetically modified Bt toxins Cry1AbMod and Cry1AcMod effectively countered resistance to native Bt toxins Cry1Ab and Cry1Ac in some pests, including pink bollworm (Pectinophora gossypiella). Here we report that Cry1AbMod and Cry1AcMod were also effective against a laboratory-selected strain of pink bollworm resistant to Cry2Ab as well as to Cry1Ab and Cry1Ac. Resistance ratios based on the concentration of toxin killing 50% of larvae for the resistant strain relative to a susceptible strain were 210 for Cry2Ab, 270 for Cry1Ab, and 310 for Cry1Ac, but only 1.6 for Cry1AbMod and 2.1 for Cry1AcMod. To evaluate the interactions among toxins, we tested combinations of Cry1AbMod, Cry1Ac, and Cry2Ab. For both the resistant and susceptible strains, the net results across all concentrations tested showed slight but significant synergism between Cry1AbMod and Cry2Ab, whereas the other combinations of toxins did not show consistent synergism or antagonism. The results suggest that the modified toxins might be useful for controlling populations of pink bollworm resistant to Cry1Ac, Cry2Ab, or both.